Short-term visual deprivation reduces interference effects of task-irrelevant facial expressions on affective prosody judgments - Fengler, Ineke; Nava, Elena; Röder, Brigitte (Frontiers in Integrative Neuroscience, 2015)
Several studies have suggested that neuroplasticity can be triggered by short-term visual deprivation in healthy adults. Specifically, these studies have provided evidence that visual deprivation reversibly affects basic perceptual abilities. The present study investigated the long-lasting effects of short-term visual deprivation on emotion perception. To this aim, we visually deprived a group of young healthy adults, age-matched with a group of non-deprived controls, for 3 hours and tested them before and after visual deprivation (i.e., after 8 h on average and at 4 week follow-up) on an audio-visual (i.e., faces and voices) emotion discrimination task. To observe changes at the level of basic perceptual skills, we additionally employed a simple audio-visual (i.e., tone bursts and light flashes) discrimination task and two unimodal (one auditory and one visual) perceptual threshold measures. During the 3 h period, both groups performed a series of auditory tasks. To exclude the possibility that changes in emotion discrimination may emerge as a consequence of the exposure to auditory stimulation during the 3 h stay in the dark, we visually deprived an additional group of age-matched participants who concurrently performed unrelated (i.e., tactile) tasks to the later tested abilities. The two visually deprived groups showed enhanced affective prosodic discrimination abilities in the context of incongruent facial expressions following the period of visual deprivation; this effect was partially maintained until follow-up. By contrast, no changes were observed in affective facial expression discrimination and in the basic perception tasks in any group. These findings suggest that short-term visual deprivation per se triggers a reweighting of visual and auditory emotional cues, which seem to possibly prevail for longer durations.